2000
DOI: 10.1021/jo000992r
|View full text |Cite
|
Sign up to set email alerts
|

Formal Hydride Transfer Mechanism for Photoreduction of 3-Phenylquinoxalin-2-ones by Amines. Association of 3-Phenylquinoxalin-2-one with Aliphatic Amines

Abstract: The photophysical and photochemical behavior of 1-methyl-3-phenylquinoxalin-2-one (MeNQ) and 3-phenylquinoxalin-2-one (HNQ) in the presence of amines is reported. While HNQ fluorescence shows an auxochromic effect and a bathochromic shift with added amines, explained by association of HNQ with amine in the ground state and emission from both excited species HNQ and [HNQ-amine], both MeNQ and HNQ are photoreduced efficiently on irradiation in the presence of amines, leading to the semireduced quinoxalin-2-ones,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 37 publications
(86 reference statements)
10
29
0
Order By: Relevance
“…(2). The quinoxalin-2-one radical anion 1 •À is similar to those reported previously as intermediaries by us for the amine photoreduction of 3-phenyl-quinoxalin-2-ones (19,20).…”
Section: Steady-state Photolysissupporting
confidence: 87%
See 3 more Smart Citations
“…(2). The quinoxalin-2-one radical anion 1 •À is similar to those reported previously as intermediaries by us for the amine photoreduction of 3-phenyl-quinoxalin-2-ones (19,20).…”
Section: Steady-state Photolysissupporting
confidence: 87%
“…Positive q values, similar to those obtained in this work, have been related to radical addition reactions of alkyl radicals to the aromatic nuclei of substituted toluenes (31), to aminoxyl radical addition to arylketenes (32), to the ratio between addition and electron abstraction on aromatic rings (33)(34)(35) and to the addition of thiyl radicals to vinyl monomers (36,37). Taking into account the stepwise photoreduction reported for 3phenyl-quinoxalin-2-ones (19,20), the lack of any photoreaction for 1a-f derivatives in aerated samples, and some laser flash photolysis results (vide infra) that showed that the first step of photoreaction is mainly a one electron transfer from the NPG, as PhNHCH 2 COO À , to the excited triplet state of the substituted 3-methyl-quinoxalin-2-one, 3 1, it can be proposed that the formation of a ion radical pair, Eq. (1) is the first step of the photoreaction.…”
Section: Steady-state Photolysissupporting
confidence: 82%
See 2 more Smart Citations
“…The photophysical and photochemical behavior of 1-methyl-3-phenyl-quinoxalin-2-one and 3-phenyl-quinoxalin-2-one in the presence of amines has been reported in some selected organic solvents (acetonitrile, methanol and hexane) (De la Fuente et al, 2002;De la Fuente et al, 2000). Spectral and kinetic characteristics of the intermediate species: triplet ion-radical pairs (Q  /amine  ) and hydrogenated neutral radicals (QH  ) have been obtained by laser flash photolysis (De la Fuente et al, 2002).…”
mentioning
confidence: 99%